Preliminary Norms Of Translating Arab Spring Dystopian Novels To English: A Paratextual Analysis Of The Queue And Seasons Of Martyrdom Novels - Alharahsheh, Abdelrauof; Kumar, Tribhuwan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Translated Arabic novels provide insight into the social, cultural, and identity aspects of Arab nations, yet translating these works is complex due to cultural nuances and varying norms. This research explores the preliminary norms influencing the selection and translation of Arabic novels into English post-Arab Spring, using The Queue by Basma Abdel Aziz (2013, translated 2016) and Season of Martyrdom by Jamal Naji (2015, translated 2016) as case studies. Applying Toury’s (2012) theory of translation norms, the study shows how social, educational, and political factors shape translation choices and impact cross-cultural communication. The study explores how sociopolitical contexts, market demands, and publishing trends shape which narratives are deemed suitable for translation and how these choices reflect broader global perceptions of the Arab world. The analysis employs Gideon Toury’s Descriptive Translation Studies (DTS) framework, focusing on both preliminary norms—such as selection criteria and translation policies—and paratextual elements, including cover design, prefaces, and promotional material, which impact the reception and interpretation of the translated works. The findings reveal that the selected novels are framed to emphasize themes of resistance, identity, and reform, highlighting the complex interplay between literature, politics, and translation. This research contributes to a deeper understanding of the role of translation in shaping the global literary representation of the Arab Spring.